2013
DOI: 10.2217/rme.13.30
|View full text |Cite
|
Sign up to set email alerts
|

3D Reconstitution of Nerve–Blood Vessel Networks Using Skeletal Muscle-Derived Multipotent Stem Cell Sheet Pellets

Abstract: These results indicate that the vigorous skeletal myogenic potential of Sk-MSCs was clearly reduced in the sheet pellet preparation and this method may be a useful adjuvant for nerve-vascular regeneration in various tissue engineering applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 35 publications
5
31
0
Order By: Relevance
“…Interestingly, we found that CD31‐positive cells also expressed GFP in both transverse mid‐segment and longitudinal sections (Figure ). The capacity of MDSCs to promote angiogenesis in vivo through growth factor secretion and differentiation into endothelial cells has been suggested in previous studies . Our results confirmed that grafted MDSCs turn into vascular endothelial cells forming newborn vessels to benefit injured nerve regeneration.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, we found that CD31‐positive cells also expressed GFP in both transverse mid‐segment and longitudinal sections (Figure ). The capacity of MDSCs to promote angiogenesis in vivo through growth factor secretion and differentiation into endothelial cells has been suggested in previous studies . Our results confirmed that grafted MDSCs turn into vascular endothelial cells forming newborn vessels to benefit injured nerve regeneration.…”
Section: Discussionsupporting
confidence: 89%
“…Cell differentiation into Schwann cells, perineurial/endoneurial cells, vascular endothelial cells and pericytes, and fibroblasts were mainly observed. Immunoelectron microscopy was performed as described previously [8, 9, 16, 17, 19, 21]. Consequently, the HNA-positive cells were detected as cells having dark nuclei because of products that reacted with DAB (black dots) in the immunoelectron micrograph.…”
Section: Methodsmentioning
confidence: 99%
“…Since nephrons are largely of mesenchymal origin and stromal cells are of crucial importance for signaling leading to the differentiation of both nephrons and collecting ducts, MSCs are undifferentiated adult cells and may be isolated from bone marrow, umbilical cord, adipose tissue, placenta, synovium, and skeletal muscle [10–14]. They are characterized by three main criteria: (a) the ability to differentiate into osteoblasts, adipocytes, and chondroblasts in vitro ; (b) the expression of surface markers CD73, CD90, and CD105; lack of expression of haematopoietic markers including CD34 and CD45; (c) plastic adherence in culture [15].…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%